2014
DOI: 10.1371/journal.pone.0106602
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Structural Remodeling in Heart Failure Modulate Arrhythmogenesis. 1D Simulation Study

Abstract: BackgroundHeart failure is a final common pathway or descriptor for various cardiac pathologies. It is associated with sudden cardiac death, which is frequently caused by ventricular arrhythmias. Electrophysiological remodeling, intercellular uncoupling, fibrosis and autonomic imbalance have been identified as major arrhythmogenic factors in heart failure etiology and progression.ObjectiveIn this study we investigate in silico the role of electrophysiological and structural heart failure remodeling on the modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 94 publications
4
58
0
1
Order By: Relevance
“…This is where computational studies are of great help by performing mechanistic analyses using mathematical models of disease-specific APs in the human heart, and revealing mechanisms for arrhythmogenesis. In this way, a simulation study by Gomez et al revealed increased APD dispersion under HF conditions assuming transmural homogeneous ion channel remodeling with respect to control, regardless of the presence or absence of M cells, but decreased TDR values were found when transmural heterogeneous remodeling was considered [53] and only in the absence of M cells. This computational study explained the above mentioned experimental controversial findings for TDR in HF, showing that the absence of M cells in the human failing heart is important but not sufficient to bring TDR values below those of nonfailing hearts.…”
Section: Altered Substrate In Hfmentioning
confidence: 95%
See 2 more Smart Citations
“…This is where computational studies are of great help by performing mechanistic analyses using mathematical models of disease-specific APs in the human heart, and revealing mechanisms for arrhythmogenesis. In this way, a simulation study by Gomez et al revealed increased APD dispersion under HF conditions assuming transmural homogeneous ion channel remodeling with respect to control, regardless of the presence or absence of M cells, but decreased TDR values were found when transmural heterogeneous remodeling was considered [53] and only in the absence of M cells. This computational study explained the above mentioned experimental controversial findings for TDR in HF, showing that the absence of M cells in the human failing heart is important but not sufficient to bring TDR values below those of nonfailing hearts.…”
Section: Altered Substrate In Hfmentioning
confidence: 95%
“…The consideration of I NaL in computational models of heart failure is crucial in simulating the activity of failing ventricular cells because of its important role in repolarization abnormalities, such as EAD generation [31,32,34,35,41,53]. Model predictions have suggested I NaL as a novel [38] Dog ↓66% ↑75% ↓33% ↓68% Puglisi et al [25] Rabbit ↓36% ↑100% ↓49% ↓24% Shannon et al [26] Rabbit ↑100% ↓50% Morita et al [39] Rabbit ↑200% ↑200% ↓20% Priebe and…”
Section: Increased Late Sodium Current (I Nal ) In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…5f). 23 a variant of the O'Hara model was constructed to reproduce molecular and physiological alterations observed in heart failure (HF). Altered parameters (see Table S5) reflected well-described changes in HF such as reduced SERCA pump activity, upregulation of NCX, and downregulation of I Ks .…”
Section: A Multivariable Regression Model Can Translate Drug Responsementioning
confidence: 99%
“…These computational studies rely on detailed and comprehensive mathematical models of action potentials for different animal species [6][7][8], including human [9]. Using this models, different studies have attempted to characterize the influence of the different sarcolemmal and SR ionic currents in AP and intracellular Ca 2+ preclinical biomarkers [10,11], but none of them has been carried out in dog, an animal that has widely been used in the past for drug and mutation effect studies [12,13].In this study, we have used a well-known existing model of the action potential and ionic currents of a dog ventricular myocyte [7] to perform a sensitivity analysis to elucidate the ionic mechanisms that affect intracellular Ca 2+ regulation. …”
mentioning
confidence: 99%